Carbon Based PV: n-Si(100)/DLC Structure for Photovoltaic Application. (8th September 2013) - Ghosh, D.; Ghosh, B.; Ghosh, Anindita; Hussain, S.; Bhar, R.; Pal, A. K.
Abstract : Diamond-like carbon films were electrodeposited on n-Si substrate to realize an n-Si/DLC PV structure. The films thus obtained were characterized by FESEM, XPS, FTIR, and Raman studies. Solar cell characteristics were also investigated critically. Maximum efficiency of 3.7% was obtained for the best n-Si(100)/DLC structure. Carrier life time was obtained from V o c decay measurement. It was observed that photoinduced charge separation in n-Si(100)/DLC structure was associated with an increase in the dielectric constant and a decrease in the device resistance. The process, being reproducible, cheap, and scalable, involving significantly less process steps, is likely to usher a new hope to the current competitive scenario of PV technology.